2015
DOI: 10.5430/cns.v4n1p57
|View full text |Cite
|
Sign up to set email alerts
|

Family members’ involvement in the care of critically ill patients in two intensive care units in an acute hospital in Bahrain: The experiences and perspectives of family members’ and nurses’ - A qualitative study

Abstract: Objective: Family can play a vital role in promoting the overall well-being of the critically ill patient. Despite this positive attribute, some nurses, for various reasons are hesitant to include family in patient care. The study explored family members and nurses' perspectives and experiences of family involvement in caring for patients in intensive care units. The objectives were to describe both nurses and family members' perspectives and experiences of family involvement in care. Methods: A descriptive ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 35 publications
3
53
1
2
Order By: Relevance
“…Such closeness allows FMs to monitor the situation, track the care given to the patient and develop trust and confidence in the care. This is supported by Plakas et al [25] and also Fateel and O'Neill, [26] who reported that FMs felt a strong need to be close to the patient to see what was going on. When FMs are unable to maintain closeness to their loved one, the resulting lack of reassurance fuels negative emotions such as fear, anxiety and helplessness.…”
Section: Subconcept 2: Proximitymentioning
confidence: 69%
“…Such closeness allows FMs to monitor the situation, track the care given to the patient and develop trust and confidence in the care. This is supported by Plakas et al [25] and also Fateel and O'Neill, [26] who reported that FMs felt a strong need to be close to the patient to see what was going on. When FMs are unable to maintain closeness to their loved one, the resulting lack of reassurance fuels negative emotions such as fear, anxiety and helplessness.…”
Section: Subconcept 2: Proximitymentioning
confidence: 69%
“…This culture is particularly evident even in the hospital. To most nurses, the family is crucial in improving patient care (Karlsson, Bergbom, & Forsberg, ; Al‐Mutair et al, ) as they aid in performing basic tasks, can give reliable patient information (Fateel & O'Niell, ), and provide comfort to patient (Karlsson et al, ). To add to this, family involvement is an integral component of patient‐centred care, a health care concept which has received growing attention to promote positive patient outcomes (Saha, Beach, & Cooper, ).…”
Section: Discussionmentioning
confidence: 99%
“…The different attributes of communication and their respective levels were selected after exhaustive literature review (Hoffman, 2009;Grossbach, Stranberg, & Chlan, 2011;Happ et al, 2011;Khalaila et al, 2011;Broyles et al, 2012;Radtke et al, 2012;Al-Mutair et al, 2013;De Jesus et al, 2013;Mirenda, 2013;Nilsen et al, 2013;Hajizadeh, Uhler, & Perez Figueroa, 2014;Robinson et al, 2014;Gaspar et al, 2015;Mathew et al, 2015;Vento-Wilson et al, 2015;Farrell, 2016;Fateel & O'Neill, 2016). From several potential characteristics, four modifiable attributes were selected (Table 1).…”
Section: Data Measuresmentioning
confidence: 99%
“…There is limited critical care literature on patient and family-centred model of delivering care while the studies conducted in this area indicate a dissatisfaction of family members in the nature and extent of involvement in the patients' care [3]. Restricted involvement in patient care activities becomes challenging to close family members when assuming the expected roles when the family member returns home [11]. Although there is little literature on involvement of family members in Kenya, primary care nurses in KNH CCUs include a component of family in the care plans but little is documented on what care families receive or to what extent they are involved in the care.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Studies conducted in Bahrain and Malawi showed that there were no policies on involvement and nurses expressed a need for a clear policy outlining the extent to which family members' can get involved in the care, the limitations during family visits and participation in care as well as guiding policies on providing support to ICU patients' family members [11,18]. Although a study in four ICUs in South Africa showed there were policies to guide involvement, some nurses would determine what to share depending on what they were willing or not willing to discuss with families.…”
Section: Involvement Policiesmentioning
confidence: 99%